BAGAIMANA AGAR PENYANDANG TUNADAKSA MAMPU MENJADI PRIBADI YANG BAHAGIA ? - Alni Junita Angriyani; Dwi Oktapia; Riko Mulyo; Muhammad liyosan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Being disabled as an adult or not since birth can have a big psychological impact on people with disabilities such as being hopeless or unable to accept their condition. This study aims to analyze the factors that affect the welfare of disabled people due to accidents. This research uses a qualitative approach with the instrumental case study method. The participants in this study were two men with disabilities due to an accident. Data collection techniques using in-depth interview techniques. The collected data were analyzed using thematic analysis techniques. The results of the study show that social support is an important factor determining the welfare of disabled people after an accident. Family support and social networks (friends and members of the disabled disabled community) can raise the spirit of life for disabled people after an accident and can make their lives happier.